Get detailed and accurate responses to your questions on IDNLearn.com. Our platform offers comprehensive and accurate responses to help you make informed decisions on any topic.

What is the solution to 8x minus 3(2x minus 4) = 3(x minus 6)

Sagot :

Answer:

x = 30.

Step-by-step explanation:

8x - 3(2x - 4) = 3(x - 6)

8x - 3*2x + - 3*-4 = 3*x + 3 * -6

8x - 6x + 12 = 3x - 18

2x + 12 = 3x - 18

2x - 3x  + 12 = 3x - 3x - 18

-x + 12 = -18

-x + 12 - 12 = -18 - 12

-x = -33

-x/-1 = -30/-1

x = 30.

Answer:

[tex]x=30[/tex]

Step-by-step explanation:

[tex]8x-3\left(2x-4\right)=3\left(x-6\right)[/tex]

First, we will expand [tex]-3\left(2x-4\right)[/tex] by applying the distributive property:

[tex]-3\times \:2x-\left(-3\right)\times \:4[/tex]

** [tex]-\left(-a\right)=a[/tex]

[tex]-6x+12[/tex]

[tex]8x-6x+12=3\left(x-6\right)[/tex]

Expand, [tex]3\left(x-6\right):[/tex]

[tex]3x-3\times \:6[/tex]

[tex]3x-18[/tex]

[tex]2x+12=3x-18[/tex]

Subtract 12 from both sides:

[tex]2x+12-12=3x-18-12[/tex]

[tex]2x=3x-30[/tex]

Subtract 3x from both sides:

[tex]2x-3x=3x-30-3x[/tex]

[tex]-x=-30[/tex]

Divide both sides by -1:

[tex]\frac{-x}{-1}=\frac{-30}{-1}[/tex]

[tex]x=30[/tex]

________________________